“Incidencia de patologías reproductivas en vacas lecheras en las parroquias del Cantón Pujilí. - Bautista Lloacana, Brissa Soledad (2024)
Nowadays, reproductive pathologies in dairy cows represent productive and economic losses in the bovine production of our country, among the most important diseases are anestrus, metritis, and ovarian cysts. Thus, the main objective of this research is to determine the prevalence and factors associated with reproductive pathologies in the parishes of Pujilí using records and diagnostic methods such as rectal palpation and ultrasonography. Therefore, the research was carried out in La Matriz parish and La Victoria parish, Pujilí canton, Cotopaxi province in 22 bovine females that are of the UTCGenEc project. Based on the above-mentioned, gynecological checkups and surveys related to feeding, supplementation, and climatic season of each of the animals were carried out. Consequently, there were 59,09% anestrus animals, 13,64% infantilism, 13,64% metritis, and 13,64% ovarian cysts. Regarding the associated external factors, a significant minor association (p-value <0.05) was found between fedd deficiency, mineral supplementation, and body condition. Finally, it is considered necessary to perform regular gynecological control to verify the reproductive status.